Pengaruh Bank Sampah Terhadap Pemberdayaan Ibu Rumah Tangga (Studi Kasus di Bank Sampah Kurabu Kota Padang Panjang) - Anno Suliza; Fery Andrianus; Chairul Chairul (Universitas Kadiri, 2020)
Waste Bank is a waste management based recycling management program that is driven by the active role and participation of members or customers. The community group with the status of Housewives are considered to have more potential resources for activities in the Waste Bank, while customer empowerment is the main indicator of the success of the program. The city of Padang Panjang still has a high final waste disposal ratio despite having a Waste Bank. The research objective is to analyze several variables so that they can influence the empowerment of Housewives. The number of respondents was 74 people taken by purposive sampling from the Kurabu Waste Bank in the city of Padang Panjang. The results of the analysis by the SEM-PLS method showed that there was a significant influence on education about the knowledge of resource utilization and the growth of an attitude of caring for the environment towards empowering customers who were housewives. Bank Sampah merupakan program manajemen pengelolaan persampahan berbasis daur ulang yang digerakkan oleh peran dan partisipasi aktif anggota atau nasabahnya. Kelompok masyarakat berstatus Ibu Rumah Tangga (IRT) dinilai memiliki potensi sumber daya yang lebih untuk berkegiatan di Bank Sampah, sedangkan pemberdayaan nasabah menjadi indikator utama keberhasilan program tersebut. Kota Padang Panjang masih mempunyai rasio beban buangan akhir sampah yang cukup tinggi meskipun telah memiliki Bank Sampah. Tujuan penelitian untuk menganalisis beberapa variabel sehingga dapat mempengaruhi pemberdayaan Ibu Rumah Tangga. Jumlah responden sebanyak 74 orang diambil dengan purposive sampling dari Bank Sampah Kurabu di Kota Padang Panjang. Hasil analisis dengan metode SEM-PLS menunjukkan terdapat pengaruh signifikan dari edukasi tentang pengetahuan pemanfaatan sumber daya dan penumbuhan sikap peduli lingkungan terhadap pemberdayaan nasabah yang berstatus Ibu Rumah Tangga.